The effect of framing and communicating COVID-19 vaccine side-effect risks on vaccine intentions for adults in the UK and the USA: a structured summary of a study protocol for a randomized controlled trial - Sudharsanan, Nikkil; Favaretti, Caterina; Hachaturyan, Violetta; Bärnighausen, Till; Vandormael, Alain (Trials, 2021)
Vaccine hesitancy is a major hurdle for stopping the COVID-19 pandemic. Recently, fear of vaccine side effects created widespread concern and paused global vaccination efforts. Many studies find that how medical risks are framed and communicated can influence individuals' perceptions and behavior, yet there is little evidence on how the communication of COVID-19 vaccine side-effect risks influences vaccine intentions. The primary objective of our study is to evaluate how the framing of vaccine-side effect risks impacts individuals' vaccine intentions and perceptions of vaccine safety. The study will assess the impact of 3 dimensions of side-effect framing:1.Qualitative risk labels: Determine whether attaching a qualitative risk label (e.g. adding "very low risk" next to the actual numerical risk) impacts individuals' willingness to take a vaccine and their perceptions of its safety.2.Comparison groups: Determine how framing side-effect risks in comparison to other causes of mortality (COVID-19 mortality and motor vehicle mortality) impacts individuals’ willingness to take a vaccine and their perceptions of its safety.3.How the comparison risks are presented: Determine whether comparisons to other causes of mortality are presented on an absolute or relative scale impacts individuals’ willingness to take a vaccine and their perceptions of its safety.
Gesehen am 03.11.2021